2021
DOI: 10.3390/plants10102214
|View full text |Cite
|
Sign up to set email alerts
|

Growth Quality and Development of Olive Plants Cultured In-Vitro under Different Illumination Regimes

Abstract: Light-emitting diodes (LEDs) are useful for the in-vitro micropropagation of plants, but little information is available on woody species. This work compares the effects of light quality and intensity on the growth and development of micropropagated olive plants from two different subspecies. Illumination was provided with fluorescent and LED lamps covering different red/blue ratios (90/10, 80/20, 70/30, 60/40) or red/blue/white combinations, as well as different light intensities (30, 34, 40, 52, 56, 84, 98 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Some scholars have studied pea seedlings, lettuce seedlings and strawberries under illumination, and found that red light can increase leaf area of pea seedlings, inhibit internode elongation of plants, promote tillering and increase the accumulation of chlorophyll, carotenoids, soluble sugar and other substances (Chen et al, 2017;Li et al, 2017;Díaz-Galián et al, 2020). Blue light is an important influencing factor of photosynthetic system activity and photosynthetic electron transfer capacity of plants, which can obviously shorten the vegetable internode spacing, promote lateral extension and reduce leaf area, and at the same time, blue light can also promote the accumulation of secondary metabolites of plants (Hitz et al, 2020;Díaz-Rueda et al, 2021). There are obvious species differences in the demand for light quality of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have studied pea seedlings, lettuce seedlings and strawberries under illumination, and found that red light can increase leaf area of pea seedlings, inhibit internode elongation of plants, promote tillering and increase the accumulation of chlorophyll, carotenoids, soluble sugar and other substances (Chen et al, 2017;Li et al, 2017;Díaz-Galián et al, 2020). Blue light is an important influencing factor of photosynthetic system activity and photosynthetic electron transfer capacity of plants, which can obviously shorten the vegetable internode spacing, promote lateral extension and reduce leaf area, and at the same time, blue light can also promote the accumulation of secondary metabolites of plants (Hitz et al, 2020;Díaz-Rueda et al, 2021). There are obvious species differences in the demand for light quality of plants.…”
Section: Introductionmentioning
confidence: 99%